2016
DOI: 10.1007/s10508-016-0836-x
|View full text |Cite
|
Sign up to set email alerts
|

Discounting of Condom-Protected Sex as a Measure of High Risk for Sexually Transmitted Infection Among College Students

Abstract: The study examined sexual delay discounting, or the devaluation of condom-protected sex in the face of delay, as a risk factor for sexually transmitted infection (STI) among college students. Participants (143 females, 117 males) completed the Sexual Delay Discounting Task (SDDT; Johnson & Bruner, 2012) and questionnaires of risky sexual behavior, risk perception, and knowledge. Participants exhibited steeper sexual delay discounting (above and beyond general likelihood of having unprotected sex) when partners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
24
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 38 publications
3
24
0
7
Order By: Relevance
“…Determining the influence of risk on condom-protected sex is especially important, given recent evidence showing uncertainty is a dynamic within-subject process, which may be highly dependent on context (Holt, Newquist, Smits, & Tiry, 2014). Although the focus of this particular manuscript was on sexual probability discounting, the data collection efforts were part of a larger study that also examined sexual delay discounting using the same sample (see Collado, Johnson, Loya, Johnson & Yi, 2017). Delay and probability discounting represent fundamentally different decision-making processes (Green & Myerson, 2004).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Determining the influence of risk on condom-protected sex is especially important, given recent evidence showing uncertainty is a dynamic within-subject process, which may be highly dependent on context (Holt, Newquist, Smits, & Tiry, 2014). Although the focus of this particular manuscript was on sexual probability discounting, the data collection efforts were part of a larger study that also examined sexual delay discounting using the same sample (see Collado, Johnson, Loya, Johnson & Yi, 2017). Delay and probability discounting represent fundamentally different decision-making processes (Green & Myerson, 2004).…”
mentioning
confidence: 99%
“…Delay and probability discounting represent fundamentally different decision-making processes (Green & Myerson, 2004). The aim of the previously published study (Collado et al 2017) was to determine if delay discounting plays a role in decisions to engage in unprotected sex. Alternatively, the aim of this study was to determine if probability discounting plays a role in decisions to engage in unprotected sex.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Inaccurate risk perception (that is, believing that one's risk is lower than it actually is) is associated with poor sexual health. Collado, Johnson, Loya, Johnson, and Yi (2017) have shown that students are less likely to use an available condom or to postpone sex until a condom becomes available if their sexual partner is seen as more desirable. The authors attribute this finding to the perception that a desirable partner is less likely to have an STI and thus, "low risk".…”
Section: Inaccurate Risk Perceptionmentioning
confidence: 99%
“…Beyond the study of pathological behavior, discounting methods have been applied to more commonplace decision-making such as academic administration (Logue & Anderson, 2001), job choice (Schoenfelder & Hantula, 2003), distribution of lottery winnings (Baker, Johnson & Bickel, 2003a), consumer behavior (Dittmar & Bond, 2010;Foxall, Doyle, Yani-de-Soriano & Wells, 2011;Hantula, Brockman & Smith, 2008), delivery options (Hantula & Bryant, 2005), everyday financial decisions such as credit card use (Fagerstrøm & Hantula, 2013), creditworthiness (Meier & Sprenger, 2012), payday and title loan choices (Mahoney & Lawyer, 2016), environmentalism and "green" choices (Arbuthnott, 2010;Hardisty & Weber, 2009), texting while driving (Hayashi, Miller, Foreman, & Wirth, 2016), preferences for sexual partners (Jarmolowicz, Lemley, Asmussen & Reed, 2015), condom use (Collado, Johnson, Loya, Johnson, & Yi, 2016), psychotherapy termination (Swift & Callahan, 2010), policy development (Plumm, Borhart & Weatherly, 2012), and health decisions (Chapman, 2002).A growing interest in delay discounting research and applications presents challenges to many behavior analysts who lack quantitative training and knowledge. Calls for increased use of quantitative methods in behavioral research and application overall have added to methodological challenges (Fisher & Lerman, 2014;Shadish, 2014).…”
mentioning
confidence: 99%